Short-term and long-term outcomes in patients with cryptococcal meningitis after ventriculoperitoneal shunt placement - Wen, Junxian; Yin, Rui; Chang, Jianbo; Chen, Yihao; Dong, Xiying; Cao, Wei; Ma, Xiaojun; Li, Taisheng; Wei, Junji (Frontiers in Neurology, 2022)
Objective The purpose of this study was to assess the short-term and long-term outcomes of ventriculoperitoneal shunt (VPS) placement in patients with cryptococcal meningitis (CM). Methods We performed a retrospective analysis of all patients with CM admitted to the Peking Union Medical College Hospital from September 1990 to January 2021. We collected related clinical features to analyze the short- and long-term outcomes of VPS at 1 month and 1 year at least the following therapy, respectively. Overall survival (OS) was compared with all patients and a subgroup of critically ill cases by the Kaplan–Meier method with the log-rank test. Univariable and multivariable analyses were also performed using the Cox proportional hazard model to identify statistically significant prognostic factors. Results We enrolled 98 patients, fifteen of whom underwent VPS. Those who received VPS had a lower cerebrospinal fluid (CSF) Cryptococcus burden (1:1 vs. 1:16; p = 0.046), lower opening pressures (173.3 mmH2 O vs. 224 mmH2O; p = 0.009) at lumbar punctures, and a lower incidence of critical cases (6.7 vs. 31.3%; p = 0.049). According to our long-term follow-up, no significant difference was shown in the Barthel Index (BI) between the two groups. Two patients in the VPS group suffered postoperative complications and had to go through another revision surgery. According to survival analysis, overall survival (OS) between the VPS and non-VPS groups was not significantly different. However, the Kaplan–Meier plots showed that critical patients with VPS had better survival in OS (p < 0.009). Multivariable analyses for critical patients showed VPS was an independent prognostic factor. Conclusion A VPS could reduce the intracranial pressure (ICP), decrease the counts of Cryptococcus neoformans by a faster rate and reduce the number of critical cases. The VPS used in critical patients with CM has a significant impact on survival, but it showed no improvement in the long-term Barthel Index (BI) vs. the conservative treatment and could lead to postoperative complications.